Allergic bronchopulmonary aspergillosis (ABPA) sans asthma: A distinct subset of ABPA with a lesser risk of exacerbation. (21st May 2019) - Muthu, Valliappan; Sehgal, Inderpaul Singh; Prasad, Kuruswamy Thurai; Dhooria, Sahajal; Aggarwal, Ashutosh N; Garg, Mandeep; Chakrabarti, Arunaloke; Agarwal, Ritesh
Abstract: Allergic bronchopulmonary aspergillosis (ABPA) is a complex immunological disorder complicating asthma. Uncommonly, ABPA presents without underlying asthma. Herein, we describe the outcomes of ABPA with and without asthma. Of the 530 subjects (median follow-up, 39 months), 37 (7%) were ABPA sans asthma. Bronchiectasis was more frequent (97.3% vs. 83.2%, P = .02), and the lung function was significantly better in ABPA sans asthma. The incidence-rate of ABPA exacerbation was higher in those with asthma than without (112 vs. 242 per 1000 person-years, P = .0001). ABPA sans asthma appears to be a distinct subset of ABPA, with a better lung function and fewer exacerbations.